Welcome to the Anthropocene - Major, Alice, 1949- (Robert Kroetsch series., 2018)
Alice Major observes the comedy and the tragedy of this human-dominated moment on Earth. Major's most persistent question--"Where do we fit in the universe?"--Is made more urgent by the ecological calamity of human-driven climate change. Her poetry leads us to question human hierarchies, loyalties, and consciousness, and challenges us to find some humility in our overblown sense of our cosmic significance. Now, welcome to the Anthropocene you battered, tilting globe. Still you gleam, a blue pearl on the necklace of the planets. This home. Clouds, oceans, life forms span it from pole to pole, within a peel of air as thin as lace lapped round an apple. Fair and fragile bounded sphere, yet strangely tough-- this world that life could never love enough. And yet its loving-care has been entrusted to a feckless species, more invested in the partial, while the total goes unnoticed. -- from "Welcome to the Anthropocene."